2006
DOI: 10.1271/bbb.60097
|View full text |Cite
|
Sign up to set email alerts
|

Red Potato Extract Protects fromD-Galactosamine-induced Liver Injury in Rats

Abstract: The protective effects of red potato extract (RPE) as to liver damage were determined in D-galactosamine (GalN)-intoxicated rats. Increases in serum aspartate aminotransferase, alanine aminotransferase, and lactate dehydrogenase activities, all of which were induced by GalN injection, decreased in RPE administered rats, suggesting that RPE acts as a functional food showing anti-hepatotoxicity.Key words: colored potato; anthocyanin; D-galactosamine; hepatotoxicity; rat It is well-known that polyphenols originat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 19 publications
(27 reference statements)
1
5
0
Order By: Relevance
“…Although the various signaling routes responsible for Mn-SOD expression are still being identified, it is believed that an increased level of Mn-SOD is cytoprotective. 27) Therefore, it is likely that the present data might support our previous report, 7) which showed that red potato extract protects against D-galactosamine-induced hepatic toxicity in rats.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…Although the various signaling routes responsible for Mn-SOD expression are still being identified, it is believed that an increased level of Mn-SOD is cytoprotective. 27) Therefore, it is likely that the present data might support our previous report, 7) which showed that red potato extract protects against D-galactosamine-induced hepatic toxicity in rats.…”
supporting
confidence: 88%
“…RPF were prepared according to our previous report. 7) Red potatoes were thoroughly washed with water and air dried on filter paper. Then they were peeled, sliced, steam-heated, mashed, dried in a drum dryer, and ground to flour.…”
mentioning
confidence: 99%
“…At the course of liver injury, the transport function of hepatocytes is distressed which can result in the leakage of plasma membrane thereby causing an increase in serum marker enzymes such as AST, ALT, ALP, and LDH (Drotman and Lawhorn, 1978;Mukherjee, 2003). GalN administration in rats disrupts the membrane permeability of the plasma membrane causing leakage of the enzymes from the cell, which leads to elevation in levels of marker enzymes (Han, et al, 2006). In our study, the rise in AST, ALT, ALP, and LDH levels induced by GalN administration was significantly reduced by ALA pretreatment suggesting that its hepatoprotective activity might be due its effect against cellular leakage and loss of functional integrity of the cell membrane in hepatocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Potatoes with anthocyanins have benefits on health. The studies with rats demonstrate anthocyanins extracted from potatoes can significantly increase SOD activity and antioxidant capacity, and protect from injury [ 3 , 4 ]. Anthocyanins in potatoes exert an anti-bacterial activity against different bacterial strains and a slight activity against three fungal strains [ 5 ].…”
Section: Introductionmentioning
confidence: 99%